Financial Risk Prediction and Entrepreneurs’ Psychological Status Under Entrepreneurial Psychology - Liang, Xiao; Yang, Ying; Ruan, Wenxi; Liu, Ji; Zhang, Bo; Xu, Zheng; Xu, Shaojun (Frontiers in Psychology, 2022)
Entrepreneurship plays an important role in the development of national economy. The study aims to accelerate the construction of social and economic structure by improving the success rate of new entrepreneurs in the process of innovation and entrepreneurship. First, the related theories of financial risk prediction are introduced, and entrepreneurial psychological status and the psychological states on entrepreneurship are analyzed. Second, the current situation of entrepreneurial psychology of new entrepreneurs is analyzed through a questionnaire survey and model test. The results show that private enterprises account for the largest proportion, with a percentage of 58.14% of 125. In total, 32 Chinese-foreign joint ventures rank second and account for 14.88% of the total, and the scale of each type of enterprises accounts for 25%, respectively. The operating years of enterprises are mainly between 10 and 20 years. Among the enterprises surveyed, the significant level of entrepreneurial psychology and entrepreneurial opportunity of entrepreneurs is p = 0.000–0.01. It indicates that males’ psychological adjustment ability and entrepreneurial ability in the entrepreneurial process are higher than females’, and their entrepreneurial psychological states and entrepreneurial ability will improve with the growth of age, education levels, and positions. It is concluded that entrepreneurial psychological capital and entrepreneurial opportunity are significantly positively correlated with financial risk expectation. The research results prove the impact of financial risks on the entrepreneurial psychology of new entrepreneurs, and provide a reference for new entrepreneurs in predicting financial risks.